INTRAVENOUS IMMUNOGLOBULIN IN PEDIATRICS - A.Yu. Shcherbina; T.G. Kosachyova; A.G. Rumyantsev ("Paediatrician" Publishers LLC, 2010)
Medications with intravenous immunoglobulin G (IVIG) had established a reputation of effective drugs in pediatric practice in treatment of initial immunodeficiency and some autoimmune and inflammatory diseases. Multiplicity of mechanisms of its effectiveness reflects physiologically many-sided functions of IgG in maintenance of organism's homeostasis. Drugs containing IVIG differ in ways of production and, correspondingly, in its formulation. The choice of the drug to the patient should be based not only on its quality but on peculiarities of patient's state. Key words: newborns, intravenous immunoglobulin, autoimmune diseases, initial immunodeficiency. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):114-118)